PELATIHAN IMPLEMENTASI MARKETPLACE UNTUK UMKM KABUPATEN CIREBON - Nuri Kartini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT Micro, Small, and Medium Enterprises or commonly abbreviated as MSMEs are business groups managed by certain individuals or business entities whose criteria are set based on Law Number 20 of 2008. Changes in consumer spending patterns not only affect large companies, but also affect businesses. small and medium enterprises (SMEs). For this reason, SMEs are required to be able to follow changes and market developments and consumer spending patterns so that their businesses can survive and develop. In response to this, the Cirebon Regency Cooperatives and UKM Office pays attention to SMEs in Cirebon with Marketplace Implementation Training located at the Apita Hotel Cirebon, on Wednesday 22 September 2021 attended by around 100 SMEs from various regions in Cirebon Regency. This training aims to socialize what it is marketplace and how to implement it. The results of the marketplace implementation training activities for SMEs that have been carried out can be concluded that: a) Participants (SMEs) who attend can understand the meaning and types of marketplaces, b) Participants (SMEs) who attend can implement marketplaces on Facebook. With the hope that after participating in the training, SMEs can create and manage a marketplace so that they can increase and develop their business. Keywords: SMEs, marketplace. e-commerce